Iskateli schastʹi︠a︡ Seekers of happiness / proizvodstvo Leningradskoĭ kino-studii "Sovetskai︠a︡ Belorusʹ" tresta Belgoskino ; avtory t︠s︡enarii︠a︡, Iogan Zelʹt︠s︡er, Grigoriĭ Kobet︠s︡ ; rezhisser-postanovshchik, V. Korsh-Sablin ; sorezhisser, I. Shapiro. - Korsh-Sablin, Uladzimir Uladzimiravich, 1900-1974; Shapiro, I. (Iosif), 1907-1989; Zelʹt︠s︡er, Iogann; Kobet︠s︡, Grigoriĭ; Bli︠u︡mentalʹ-Tamarina, M.M., 1859-1938; Zuskin, Benjamin, 1899-1952; I︠a︡rov, S. K.; Zhukovskiĭ, B. E.; Ri︠a︡bov, B.; Dunaevskiĭ, Isaak Osipovich, 1900-1955 (National Center for Jewish Film, 2007)
During the late 1920s, many impoverished Jews searching for a better life made their way to Birobidzhan, the Soviet Jewish Autonomous Region on the Chinese border. The story of a Jewish family's immigration to Birobidzhan and their experiences as settlers on a collective farm in the area. While the family encounters hardships in adjusting to this new way of life, their search for assimilation is ultimately shown as positive. While the film is essentially a Soviet propaganda piece emphasizing the utopian dream of Birobidzhan, the reality of the area was harsh and inhospitable.